Relationship between the Value Matrix and Attitudes toward Globalization among Irbid University College Students - Hazim I. Al Momani (Sultan Qaboos University, 2015)
This study aims at identifying the value matrix and its relationship with attitudes toward globalization among Irbid University college students. To achieve this aim, the researcher designed a scale for value matrix that consisted of 60 items distributed to six value domains; religious, social, economic, theoretical, aesthetic and political. A scale for the attitude toward globalization that consisted of 48 items was also designed. Both instruments were administered to a sample of 217 female students who were randomly chosen.The findings of the study indicated that the degree of the adoption of Irbid university college students of value matrix was medium. The religious values ranked first in the pyramid of value matrix: then came in sequence the social, followed by theoretical, economic, aesthetic and finally political. The findings showed that Irbid University college students' attitude toward globalization was medium. There was significantly positive correlation between the value matrix and students attitudes toward globalization. Also, the correlations between the attitude toward globalization and each of economic, theoretical, aesthetic and political values were positive. However, there were negative correlations between the attitude toward globalization and each of religious and social value domains.